Processing of Donor Human Milk: Update and Recommendations From the European Milk Bank Association (EMBA) - Moro, Guido E.; Billeaud, Claude; Rachel, Buffin; Calvo, Javier; Cavallarin, Laura; Christen, Lukas; Escuder-Vieco, Diana; Gaya, Antoni; Lembo, David; Wesolowska, Aleksandra; Arslanoglu, Sertac; Barnett, Debbie; et al. (Frontiers in Pediatrics, 2019)
Background. Mother’s own milk (MOM) is the gold standard for feeding and nutrition of preterm and term infants. When MOM is not available or is not enough, donor human milk should be used. Milk delivered to Human Milk Banks (HMBs) should be pasteurized to inactivate viral and bacterial agents. Currently, a pasteurization process at 62.5°C for 30 minutes (Holder pasteurization, HoP) is recommended in all international guidelines of HMBs. It is known that HoP affects some of the nutritional and biological components of human milk. State of the art. Some studies demonstrate that control and calibration of temperature cycle in HoP are not always applied and may contribute to the different results reported in literature. New methodologies to treat human milk able to improve the retention of nutritional and biological components while assuring at least the same microbiological safety of HoP are under evaluation. These processing techniques include High-Temperature-Short-Time (HTST) pasteurization, High Pressure Processing (HPP), and Ultraviolet-C (UV-C) irradiation. HTST is a thermal process where milk is forced between plates or pipes heated on the outside by hot water, and is heated to 72°C for 5-15 seconds. This method is well established and utilized in the dairy industry to improve the organoleptic characteristics of the final product. HPP is a nonthermal processing method that can be applied to solid and liquid foods. This technology inactivates pathogenic microorganisms by applying hydrostatic high pressure (usually 400-800 MPa) during short-term treatments (<5-10 minutes). UV irradiation utilizes short-wavelength ultraviolet radiation in the UV-C region (200-280 nm) that is harmful to microorganisms. It is effective in destroying the nucleic acids in these organisms, so that their DNA is disrupted by the UV radiation. Conclusions. This paper presents recommendations of the EMBA Working Group on “Processing of HM”. While research on the most promising technologies that in the future will represent an alternative to HoP (HTST, HPP, UV-C) is progressing, at the moment it is important to recognize that consistency and quality assurance of the pasteurizers on the market today represent a fundamental component previously lacking in the Holder approach.